Unraveling the Impact of Non-Covalent Interactions and Different Donor Moieties on Charge Transport in DPPT-Based Polymers (Communications in Computational Chemistry, 2025)
The integration of both rigid and flexible components holds great potential to significantly enhance the overallperformance of organic electronic devices. Non-covalent interactions are frequently harnessed to augment the planarconjugation of polymers, consequently elevating the rigidity of these polymers. However, the influence of the dihedralangle distortion between donor and acceptor units, which is induced by the flexibility inherent in donor-acceptorcopolymers, on charge transport remains poorly understood. In this study, we systematically investigate intra-chain chargetransport parameters and charge mobility for the 3,6-bis(thiophen-2-yl) diketopyrrolopyrrole (DPPT) conjugated withvarious donor moieties. Combining with density functional theory (DFT) and the Su-Schrieffer-Heeger (SSH) model, wefind that when the non-covalent interactions between the donor and acceptor units are enhanced (as exemplified by DPPT-FT and DPPT-BO), the coupling between electrons and low-frequency vibrations is significantly suppressed.Simultaneously, the intra-chain electronic coupling increases owing to substantial orbital overlap. Surface hoppingsimulations are utilized to study the charge transport properties. For DPPT-T, DPPT-FT, and DPPT-BT, weaker molecularrigidity and disordered chain packing lead to thermally activated hopping transport (low electronic coupling and highreorganization energy). In contrast, the enhanced structural rigidity of DPPT-BO facilitates charge delocalization, leadingto an initial improvement in carrier mobility under low-temperature conditions, and thermal fluctuation effects induce aband-like behavior at high temperature.
Keywords: charge transport; Diketopyrrolopyrrole copolymers; torsional stiffness; non-covalent interactions; Su-Schrieffer-Heeger model